Knowledge, attitude, and practice towards food safety amongst school children, food handlers and consumers: protocol for a pre-post longitudinal study in North East India - Savant, Rashmi; Singh, Rajkumar James; Hazarika, Suranjana Chaliha; Majumdar, Tapan; Dolma, Karma G.; Devi, Sarangthem Indira; Dutta, Tapan Kumar; Lyngdoh, Valerie; Modi, Dilem; Roy, Swagnik; Devi, Rajkumari Mandakini; Kylla, Hosterson; et al. (Frontiers in Public Health, 2025)
BackgroundThe North Eastern states of India exhibit a rich diversity of cultural, geographical, and traditional food practices, which, while unique and valuable, contribute to an increased susceptibility to foodborne and waterborne diseases. While these practices contribute to the region’s identity, inadequate food safety measures increase the risk of foodborne diseases, constituting a pressing public health issue.ObjectiveThis study aims to assess the knowledge, attitudes, and practices (KAP) related to food safety among school children, food handlers, and consumers in eight North Eastern (NE) states of India. It also evaluates the changes in KAP scores across all three study groups following an educational intervention program.MethodsA pre-post quasi experimental longitudinal study design involving 11 NE centres under the ICMR FoodNet program and comprising three waves:Wave 1: Baseline cross-sectional KAP assessment among school-going children (studying in 9th and 10th standard), food handlers, and consumers by using structured questionnaires adapted from WHO and CDC guidelines.Wave 2: Implementation of an educational intervention in all three study groups only, guided by a checklist. No intervention for control groups.Wave 3: Post-intervention quasi-experimental assessment of both the study and control groups to evaluate changes in KAP at one-month post-intervention, and 6 months post-intervention.Intended use of resultsThe study is expected to enhance knowledge and promote sustainable hygiene practices among participants, reduce high-risk behaviors, and foster community-level dissemination of food safety knowledge. Findings will contribute to evidence-based policymaking and support the development of a Social and Behavior Change Communication (SBCC) model for food safety. Insights from this pilot study will provide an adaptable framework to generate food safety awareness data in other regions with diverse cultural and geographical contexts. The mobile app developed for this KAP study will act as a ‘scalable tool’ by enabling field workers to efficiently collect and submit standardized KAP data across diverse settings, thereby improving consistency and moderating the logistical burden often associated with such large-scale field surveys. If effective, the app can support data collection nationwide, extending its utility beyond North East India.